2004
DOI: 10.1109/tbme.2004.827263
|View full text |Cite
|
Sign up to set email alerts
|

On the Flow Dependency of the Electrical Conductivity of Blood

Abstract: Experiments presented in the literature show that the electrical conductivity of flowing blood depends on flow velocity. The aim of this study is to extend the Maxwell-Fricke theory, developed for a dilute suspension of ellipsoidal particles in an electrolyte, to explain this flow dependency of the conductivity of blood for stationary laminar flow in a rigid cylindrical tube. Furthermore, these theoretical results are compared to earlier published measurement results. To develop the theory, we assumed that blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 20 publications
5
79
0
Order By: Relevance
“…Experiments presented in literature demonstrated that the electrical conductivity of blood depends on its velocity, i.e. the electrical conductivity of moving blood is higher than for the stationary one, Hoetink et al (2004), Balan et al (2004). This increase of the electrical conductivity is caused by reorientation of erythrocytes (red blood cells) influenced by the viscous forces, Fujii et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments presented in literature demonstrated that the electrical conductivity of blood depends on its velocity, i.e. the electrical conductivity of moving blood is higher than for the stationary one, Hoetink et al (2004), Balan et al (2004). This increase of the electrical conductivity is caused by reorientation of erythrocytes (red blood cells) influenced by the viscous forces, Fujii et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the experiments were conducted in static conditions. In flowing conditions, RBC orientation may also be an additional factor to consider [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…It is designed to be placed on any location where palpation of a pulse is possible. The vIPG system is of four wire, AC current injection type [4]. It expands the AD5933 IC by a single-ended, improved Howland current pump and a transimpedance amplifier.…”
Section: Hardwarementioning
confidence: 99%